Management of credit risks of bank - Zholamanova, M.T. (Journal of Economic Research & Business Administration, 2016)
In this article questions of definition of concept of risks and credit risks are considered. The internal and external factors influencing credit risk re-veal. Division of credit risk on direct risks and portfolio risks. Existence of an effective control system of risks is one of the most important conditions of development of business, such system is the system of a risk manage-ment of bank. For the purpose of effective management of credit risks in banks of the 2nd level new business process taking into account division of functions of sales and risk management is fulfilled, and the system of a risk management is introduced. In this regard in the present to article fea-tures management of credit risks of commercial banks, the efficiency of a risk management and factors influencing degree of credit risk reveal. The organizational structure of management of credit risks on the example of domestic banks is considered.